Pemikiran Pendidikan Buya Hamka dan Relevansinya dengan Pendidikan Islam Kontemporer - Khoir, Mulyanto Abdullah; Yulqowin, Ilma; Sangadah, Siti; Sutrisno, Agus (Lembaga Yasin AlSys, 2025)
Based on the Qur’an as the main guideline, Islamic education experts basically agree that the purpose of Islamic education is to form a human being with the personality of “Insan Kamil”. Insan Kamil is a pious individual, spiritually and physically intact, and able to live and develop naturally in accordance with his obedience to Allah SWT. Based on this background, the researcher formulates the problems that become the focus of research, namely: First, What are the main thoughts of Buya Hamka about Islamic education, second, How is the relevance of these thoughts to contemporary Islamic education. This research aims to explore Buya Hamka’s thoughts related to Islamic education and explain its application and relevance to Islamic education in the modern era. Researchers used descriptive methods with a library research approach, which is the process of collecting data or information from various sources of literature to analyze the issues discussed. The results of this study concluded several important points related to the concept of Islamic education according to Buya Hamka. First, the concept of Islamic education in Buya Hamka’s view includes three main meanings: the distribution of knowledge (ta’lim), nurturing (tarbiyah), as well as the formation of adab and potential development (ta’dib). Second, the foundation of Islamic education is the Qur’an and As-Sunnah, with educational goals that include two dimensions, namely ukhrawi (seeking the pleasure of Allah SWT) and worldly (building character and provision for social life). Third, the curriculum of Islamic education according to Buya Hamka includes religious science, rational science, social science, and skills. Fourth, educators in Buya Hamka’s view include parents, teachers, and society. Fifth, ideal learners according to Buya Hamka are individuals who have noble morals, are able to develop their potential, are humble, understand and practice learning manners, and respect and obey others. Looking at the basis and objectives of Islamic education, the concept of Islamic education according to Buya Hamka in his time remains relevant to be applied in the context of contemporary Islamic education.